Ancestors Worship Based on Timorese Perspectives in Oelbubuk Village, Central Mollo Sub-District, Timor Tengah Selatan District - Yenry Pellondou; John A Titaley (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: In 1928, Timorese in Oelbubuk had abandoned their original beliefs and converted to Christianity. Now, belief in Uis Neno (sky god) is interpreted as God, Uis Pah (earth god) is lost in meaning, while the meaning of Pah Nitu (ancestor) is still maintained. Even though they have become Christians, the worship of Pah Nitu persisted in their lives. Why is that? What is so special about Pah Nitu for Timorese? Design/methodology/approach: This study uses a descriptive qualitative approach, with data collection techniques in the form of Participant Observation, and Indepth Interview and Literature Study to answer that question. Findings: Through interviews with Tua Adat, Village Heads and Timorese in Oelbubuk, it was found that even though they had become Christians, worship of Pah Nitu was maintained, because the lives of Timorese in Oelbubuk depended entirely on the role of Pah Nitu. Research limitations/implications: Result shows existence of original belief of the Timorese in Oelbubuk centered on the belief in the existence of a celestial deity called Uis Neno. There are also other objects of worship that are considered as a manifestation of the manifestation of Uis Neno, namely Uis Pah (earth god) and Pah Nitu (ancestral spirits) Practical implications: This research shows that Pah Nitu is understood as an important figure that will not be replaced by the role of any religious teachings (including Christianity). Originality/value: This research is conducted in Oelbubuk Village, Central Mollo Sub-District, Timor Tengah Selatan District. Paper type: Research paper.